Chat Reference Service: An Analysis of one Semester's Data. - JoAnn Sears (Issues in Science and Technology Librarianship, 2001)
Four months of chat reference questions received at a centralized reference services desk of an ARL library are analyzed in this study. Types of questions and types of users (when identified) are investigated. This study examines whether the questions were localized to the specific library's resources/services as well as whether the person responding to the chat question gave any evidence of consulting resources during the course of the chat session. Suggestions for further areas of research are also included.